Modelling and simulation of fuel cell/photovoltaic hybrid power system - Aseeri, Ahmed (Cranfield University, 2012)
Due to an ever increasing demand for power consumption and a rising public awareness of the impact on the environment, renewable energy based on Hybrid Power Systems (HPS) (e.g. fuel cell, wind or solar) to supply electricity has attracted a growing research interest. Photovoltaic (PV) power generation systems are among the most promising renewable energy technology solutions. Fuel Cell (FC), on the other hand, is emission-free and quieter than hydrocarbon fuel-powered engines. It saves fuel and is cleaner for the environment. Such systems can generate electricity from clean sources to power loads located in inaccessible or remote areas. The aim of this thesis is to investigate the potential for utilising an FC/PV hybrid power system to provide power for a water pump, which supply an elevated water tank (6,500 litres/day consumption) to a small community located in a remote area. The HPS consists of a photovoltaic solar panel, a 1.2 KW Nexa Proton Exchange Membrane Fuel Cell (PEMFC), a Lead acid battery bank, a bidirectional DC/DC converter, one directional DC/DC converter and a water pump. The thesis will commence with a literature review, giving an overview of energy demand and future trend, describing the different HPS configurations and giving some examples of similar projects carried out by other researchers and organisations. A system component description is also covered. The thesis will then move on to describing the HPS simulation model development using Matlab/Simulink simulation environment, concluding with the test cases used to validate the model based on the 1.2 KW Nexa PEMFC and PV panels. In the case study, the system utilizes photovoltaic (PV) as the primary power generator, PEMFC as the secondary back-up power generator and a battery bank (to store any excess power) as power storage device. The advantage of the proposed system is that, in addition to being environmentally friendly, it also has lower maintenance costs, noise and carbon footprint. Two main scenarios were explored to validate the hybrid system performance, at two different geographical and environmental conditions. The first case is based in Saudi Arabia, where it is hot and sunny for most of the year. This scenario permits higher utilization of the power generated from the PV cells and reduces the dependence on power produced by the fuel cell. The second case scenario is based in the UK, where it is cold and cloudy for most of the year. The Sunlight here is at minimum, leading to higher dependence on the fuel cells for the system operation.